Insecticide resistance status and mechanisms in Aedes aegypti populations from Senegal. - Ndeye Marie Sene; Konstantinos Mavridis; El Hadji Ndiaye; Cheikh Tidiane Diagne; Alioune Gaye; El Hadji Malick Ngom; Yamar Ba; Diawo Diallo; John Vontas; Ibrahima Dia; Mawlouth Diallo (Public Library of Science (PLoS), 2021)
Aedes aegypti is the main epidemic vector of arboviruses in Africa. In Senegal, control activities are mainly limited to mitigation of epidemics, with limited information available for Ae. aegypti populations. A better understanding of the current Ae. aegypti susceptibility status to various insecticides and relevant resistance mechanisms involved is needed for the implementation of effective vector control strategies. The present study focuses on the detection of insecticide resistance and reveals the related mechanisms in Ae. aegypti populations from Senegal. Bioassays were performed on Ae. aegypti adults from nine Senegalese localities (Matam, Louga, Barkedji, Ziguinchor, Mbour, Fatick, Dakar, Kédougou and Touba). Mosquitoes were exposed to four classes of insecticides using the standard WHO protocols. Resistance mechanisms were investigated by genotyping for pyrethroid target site resistance mutations (V1016G, V1016I, F1534C and S989P) and measuring gene expression levels of key detoxification genes (CYP6BB2, CYP9J26, CYP9J28, CYP9J32, CYP9M6, CCEae3a and GSTD4). All collected populations were resistant to DDT and carbamates except for the ones in Matam (Northern region). Resistance to permethrin was uniformly detected in mosquitoes from all areas. Except for Barkédji and Touba, all populations were characterized by a susceptibility to 0.75% Permethrin. Susceptibility to type II pyrethroids was detected only in the Southern regions (Kédougou and Ziguinchor). All mosquito populations were susceptible to 5% Malathion, but only Kédougou and Matam mosquitoes were susceptible to 0.8% Malathion. All populations were resistant to 0.05% Pirimiphos-methyl, whereas those from Louga, Mbour and Barkédji, also exhibited resistance to 1% Fenitrothion. None of the known target site pyrethroid resistance mutations was present in the mosquito samples included in the genotyping analysis (performed in > 1500 samples). In contrast, a remarkably high (20-70-fold) overexpression of major detoxification genes was observed, suggesting that insecticide resistance is mostly mediated through metabolic mechanisms. These data provide important evidence to support dengue vector control in Senegal.